SIMILAR EFFICACY OF TOFACITINIB ON DISEASE ACTIVITY IN RHEUMATOID ARTHRITIS PATIENTS WITH AND WITHOUT PREVIOUS BIOLOGICALS; RESULTS FROM THE TURKBIO REGISTRY - Zengin, B.; Inanc, N.; Akar, S.; Can, G.; Dalkilic, E.; Tufan, A.; Onen, F. (Bmj Publishing Group, 2018)
[Abstract Not Available]
Congress of the European-League-Against-Rheumatism (EULAR) -- JUN 13-16, 2018 -- Amsterdam, NETHERLANDS